Método da altura relativa aplicado a indivíduos de Pinus taeda L. - Novaes, Davidson da Silva (2023)
The management of planted forests with species of the genus Pinus requires, among the fundamental tools for this purpose, that measurements be performed with the greatest possible precision. However, such practices can involve high costs and time, which demands research and development of measurement methods that are faster, cheaper and equally precise. This study aimed to evaluate the estimates of diameter and volume, obtained by the Relative Height Method, in comparison with the Smalian Method observed through the cubing of sample trees, in a Pinus taeda L. stand. Data from 65 trees of the species, planted in the South-Central region of Paraná, in Irati, with ages ranging from 7.5 to 29.5 years, were used. Volume calculations were performed using the relative height methods, which were compared with the volume obtained by the Smalian method. The comparison was made using the following criteria: Mean Percentage Deviation (MDP%), Bias, linear correlation (r_(Y Ŷ)) and standard error of the estimate (s_(Y Ŷ)), between observed and estimated values of diameter and volume along the trunk of the 65 trees. The data were subjected to statistical analyses using the t-test for paired data, the F-test and the precision (P%), obtained by the Chi-square test. There was no significant difference between the diameters measured in the positions suggested by Smalian and the Relative Height Method, a fact that makes this last method a possibility for cubing standing trees. Regarding the performance of the Relative Height Method between volumetric models and shape factors, there were no advantages in using the tested method, and any one can be used with the same relative precision. The regions of the trunk that presented the highest standard error value for the volume were: between the relative height and total height, followed by the region of DBH and relative height and, finally, the region between zero height and DBH. For volume estimates, the relative height method presented a slight overestimation of the values for the trees studied.